Head of Gold, Feet of Clay: The Online Learning Paradox - Power, Michael; Gould-Morven, Anthony (International Review of Research in Open and Distributed Learning, 2011)
Although online learning (OL) is becoming widely accessible and is often viewed as cutting-edge, the actual number of regular faculty participating in this form of teaching remains small. Moreover, OL, despite its growing recognition, is often associated with high rates of student dissatisfaction and isolation, withdrawal, and attrition. Furthermore, although administrators typically champion support of OL, they often seem unable or unwilling to marshal the necessary financial, human, and technological resources to produce high-quality course materials and to effect efficient course delivery. In short, online learning seems paradoxically to be both booming and busting simultaneously. It is expanding supply yet hitting similar obstacles that distance education encountered generations earlier. Under these circumstances, OL is unlikely to become mainstream without a major redirection. This article applies economic principles and concepts to OL. The revised conceptualization posits that an understanding of stakeholder priorities is the key to improved online course design and delivery.